Health-promoting properties of artichoke in preventing cardiovascular disease by its lipidic and glycemic-reducing action - Mariangela Rondanelli; Francesca Monteferrario; Simone Perna; Milena Anna Faliva; Annalisa Opizzi (Monaldi Archives for Chest Disease, 2015)
The artichoke, Cynara scolymus, is one of the most ancient plants grown in the world, and its extracts, obtained from different parts of the plant (leaves, fruits and roots), have been used as medicaments from time immemorial. The pharmacological and therapeutic effects of the artichoke on the liver had already been well known in the 17th century. Modern studies started in the last century confirmed the stimulating properties of artichoke extracts on the liver and gallbladder. The ensuing wave of research was initially focused on the patent liver-stimulating, diuretic and choleretic effects exerted by artichoke preparations on both animals and man, then discovering such other therapeutic properties as the hypolipemizing activity, antioxidant activity and hypoglycemizing activity. This review enumerates the most significant studies that have highlighted these therapeutic properties. Complementary medicine information needs to be incorporated into clinical practice and patient and professional education, in addition to adequate education about proper nutrition. Awareness of the widespread use of complementary and alternative medicine by people with metabolic disorders is crucial for healthcare professionals in order to prevent cardiovascular disease.